ANALISIS KEMAMPUAN PEMECAHAN MASALAH DAN PENALARAN MATEMATIK SERTA SELF-EFFICACY SISWA SMA - Siti Zakiyah; Syifa Halawatul Imania; Gustiani Rahayu; Wahyu Hidayat (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
The aims of this research are to know about mathematical problem-solving ability student of senior high school towards trigonometry material, mathematical reasoning ability student of senior high school towards the statistical material, and self-efficacy ability in mathematics learning students of a senior high school. The research used descriptive qualitative research, and the research object is XI IPA of senior high school. The chosen students are students who have learned about trigonometry and statistic. The chosen students who become sample are 30 students. In this research, the technic used tests, with the instruments used are question and questionnaire. The test consists of 5 question about mathematics problem-solving, 5 question of mathematical reasoning, and 40 questionnaires of self-efficacy ability. According to the results of our research, it can be concluded that the students' ability in problem-solving and reasoning mathematics is low, while students' ability in self-efficacy is good. It can be seen that the students have good self-efficacy ability along with the problem-solving ability and reasoning ability that are still low.